MANAJEMEN PENGETAHUAN DALAM MENINGKATKAN MUTU LEMBAGA PENDIDIKAN ISLAM - Sauqi Futaqi (TA'LIM : Jurnal Studi Pendidikan Islam, 2020)
This paper seeks to offer a conceptual framework regarding knowledge management in order to improve the quality of Islamic education institutions. This concept is very interesting because it creates a knowledge-based institutional culture. In addition, with this knowledge management concept, educational institutions will find it easier to run the wheels of the organization, especially when there is a change of leadership. Through activities of finding, selecting, sharing, and storing knowledge, a culture of quality will be created in Islamic educational institutions.